Sosialisasi BPJS Ketenagakerjaan bagi Komunitas Sahabat UMKM Pamulang di Kecamatan Pamulang, Kota Tangerang Selatan - Jaya, Yozar Putra; Rifa'i , Achmad; Priastiwi , Dian; Sari; Sofatunisa Ramdayani , Syofia (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
The Social Security Administering Body for Employment (BPJS Ketenagakerjaan) plays a strategic role in providing protection for workers in the informal sector, including micro, small, and medium enterprises (MSMEs) that are vulnerable to work-related risks. However, the level of understanding and participation of MSME actors in this program remains low. This community service activity aims to increase literacy and awareness among MSME actors within the Sahabat UMKM Pamulang Community (SUP) in the Pamulang District, South Tangerang City, regarding the BPJS Ketenagakerjaan program. The implementation method was carried out through interactive socialization that included material presentation, group discussions, and direct question-and-answer sessions with participants. The material presented covered the introduction of the Old Age Security (JHT), Work Accident Security (JKK), Death Security (JKM) programs, and the procedures for registering as an independent participant. The results of this activity showed an increase in the interest of MSME actors to become independent participants in BPJS Ketenagakerjaan. This activity demonstrates that a communicative and community-based socialization approach is effective in increasing social security literacy among MSME actors. It is expected that follow-up activities can be conducted regularly with the support of related institutions to expand the coverage of employment protection for the informal sector.